Advancements in research on the association between the biological CLOCK and type 2 diabetes - Cheng, Hui; Zhong, Dayuan; Tan, Yimei; Huang, Menghe; Xijie, Sun; Pan, Hong; Yang, Zixian; Huang, Fangmei; Li, Feifan; Tang, Qizhi (Frontiers in Endocrinology, 2024)
Due to the Earth's rotation, the natural environment exhibits a light-dark diurnal cycle close to 24 hours. To adapt to this energy intake pattern, organisms have developed a 24-hour rhythmic diurnal cycle over long periods, known as the circadian rhythm, or biological clock.With the gradual advancement of research on the biological clock, it has become increasingly evident that disruptions in the circadian rhythm are closely associated with the occurrence of type 2 diabetes (T2D). To further understand the progress of research on T2D and the biological clock, this paper reviews the correlation between the biological clock and glucose metabolism and analyzes its potential mechanisms. Based on this, we discuss the potential factors contributing to circadian rhythm disruption and their impact on the risk of developing T2D, aiming to explore new possible intervention measures for the prevention and treatment of T2D in the future.